Proteus genus sensitivity testing for various classes of antibiotics. - Abdulrraziq, Ahmed A.; Salih, Sami M. (Scientific Journal for Faculty of Science-Sirte University, 2023)
Proteus genus has become one of the most common pathogens in Libya, with high antibiotic resistance, which can lead to medical problems in many situations in hospitals. However, there is no comprehensive study of the sensitivity and resistance of Proteus pathogenic to antibiotics in Libya. Therefore, the present study was conducted with the aim to test the sensitivity and resistance of two Proteus isolates (UTI and diarrhea) to antibiotics. The Kirby-Bauer (disc diffusion) method was used to investigate the effects of eight Antibiotics, belonging to different classes. Aminoglycosides represented by Gentamicin, Tetracyclins class represented by Doxycycline 30ug, Penicillin class represented by Ampicillin 10ug, Macrolides class represented by (Azithromycin 15ug, Erythromycin 15ug), and Cephalosporins class represented by (Ceftriaxone 30ug, Ceftazidime 30ug, and Cephalexin 30ug). Antibiotic susceptibility results test revealed all proteus isolates to be resistant to most antibiotics, especially the classes (penicillin, Macrolides, Cephalosporins). In contrast, there were no significant differences between the resistance of the protease isolates from the urinary tract and the protease isolated from diarrhea. On the other hand, The antibiotic gentamicin recorded the highest sensitivity to Proteus isolates (UTI) and (diarrhea) tested at 46.6% and 39.9%, respectively. This study concludes to new antibiotics must be developed, although aminoglycosides are still effective against Proteus genus.